SUPERVISI INDIVIDUAL SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN GURU DALAM MELAKSANAKAN PEMBELAJARAN DI SMAN 1 BUNGO TAHUN PELAJARAN 2020/2021 - yulianto, hendri (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to improve the skills of teachers in implementing learning by applying individual supervision. This research is school action research (PTS) which is carried out in two cycles through procedures: (1) planning, (2) action, (3) observation, (4) reflection. The subjects of this study were 3 teachers of SMAN 1 Bungo who met the criteria and needed to be given guidance through individual supervision. Data collection techniques were carried out with observation guides, interview guides, journals of teacher and student activities, tests of teacher skills in carrying out teacher learning, and tests of measuring student learning outcomes. The increase in teacher skills in implementing learning before the action was 58.2%, the first cycle to 70.1%, and the second cycle increased again to 83.7%. The average student learning outcomes for teacher A at the beginning of 52.33, in the first cycle 54.35 and increased in the second cycle by 64.35. The average student learning outcomes for teacher B at the beginning of 49.85, in the first cycle 53.15 and increased in the second cycle by 63.15 and for teacher C at the beginning of 45.44, in the first cycle 49.85 and increased in the first cycle. II of 62.45. So it can be concluded that the skills of teachers in implementing learning have increased through the application of individual supervision.